2019
DOI: 10.1029/2018jf004758
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Coastal Foredune Ecomorphodynamics in the U.S. Pacific Northwest via Bayesian Networks

Abstract: As sea level rise and possible changes in storminess threaten coastal communities and infrastructure, the capacity for foredunes to provide protection depends on their geomorphology, which is determined by interactions between physical beach processes and vegetation. Here we use descriptive Bayesian network analyses to examine how sediment supply, beach characteristics, and two species of beachgrass (Ammophila arenaria and Ammophila breviligulata) alter foredune morphology and patterns of sand accretion on U.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 65 publications
5
48
0
Order By: Relevance
“…In particular, steeper sloped beaches, positive shoreline change rates, and higher shoot densities of both beachgrass species were all associated with taller and wider dunes. In addition, Biel et al [19] found that species-specific differences in sand capture of the two beachgrasses explained additional variability in dune shape, as had been hypothesized in other studies [11,12]. Ammophila breviligulata, which has less dense but thicker shoots, exhibited more lateral growth, resulting in greater sand deposition and widening of the foredune at the seaward margin.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…In particular, steeper sloped beaches, positive shoreline change rates, and higher shoot densities of both beachgrass species were all associated with taller and wider dunes. In addition, Biel et al [19] found that species-specific differences in sand capture of the two beachgrasses explained additional variability in dune shape, as had been hypothesized in other studies [11,12]. Ammophila breviligulata, which has less dense but thicker shoots, exhibited more lateral growth, resulting in greater sand deposition and widening of the foredune at the seaward margin.…”
Section: Introductionmentioning
confidence: 63%
“…This feedback process builds dunes, reducing vulnerability to coastal flooding and erosion [6,7], providing habitat for wildlife [8], and serving to sequester carbon [9]. One area of focus has centered on the role of species-specific biophysical feedbacks of dune plants in determining dune geomorphology [4,5,[10][11][12][13][14][15][16][17][18][19]. These studies show that vegetation functional morphology and its interaction with windblown sand can contribute to the variability in dune geomorphology at local to landscape level scales.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations